ACE Phenotyping as a Guide Toward Personalized Therapy With ACE Inhibitors. (July 2017) - Danilov, Sergei M.; Tovsky, Stan I.; Schwartz, David E.; Dull, Randal O.
Background: Angiotensin-converting enzyme (ACE) inhibitors (ACEI) are widely used in the management of cardiovascular diseases but with significant interindividual variability in the patient's response. Objectives: To investigate whether interindividual variability in the response to ACE inhibitors is explained by the "ACE phenotype"—for example, variability in plasma ACE concentration, activity, and conformation and/or the degree of ACE inhibition in each individual. Methods: The ACE phenotype was determined in plasma of 14 patients with hypertension treated chronically for 4 weeks with 40 mg enalapril (E) or 20 mg E + 16 mg candesartan (EC) and in 20 patients with hypertension treated acutely with a single dose (20 mg) of E with or without pretreatment with hydrochlorothiazide. The ACE phenotyping included (1) plasma ACE concentration; (2) ACE activity (with 2 substrates: Hip-His-Leu and Z-Phe-His-Leu and calculation of their ratio); (3) detection of ACE inhibitors in patient's blood (indicator of patient compliance) and the degree of ACE inhibition (ie, adherence); and (4) ACE conformation. Results: Enalapril reduced systolic and diastolic blood pressure in most patients; however, 20% of patients were considered nonresponders. Chronic treatment results in 40% increase in serum ACE concentrations, with the exception of 1 patient. There was a trend toward better response to ACEI among patients who had a higher plasma ACE concentration. Conclusion: Due to the fact that "20% of patients do not respond to ACEI by blood pressure drop, " the initial blood ACE level could not be a predictor of blood pressure reduction in an individual patient. However, ACE phenotyping provides important information about conformational and kinetic changes in ACE of individual patients, and this could be a reason for resistance to ACE inhibitors in some nonresponders.